The book of Exodus : composition, reception, and interpretation - Dozeman, Thomas B.; Evans, Craig A.; Lohr, Joel N. (Vetus Testamentum, Supplements, 2014)
Written by leading experts in the field, The Book of Exodus: Composition, Reception, and Interpretation offers a wide-ranging treatment of the main aspects of Exodus. Its twenty-four essays fall under four main sections. The first section contains studies of a more general nature, including the history of Exodus in critical study, Exodus in literary and historical study, as well as the function of Exodus in the Pentateuch. The second section contains commentary on or interpretation of specific passages (or sections) of Exodus, as well as essays on its formation, genres, and themes. The third section contains essays on the textual history and reception of Exodus in Judaism and Christianity. The final section explores the theologies of the book of Exodus.